Posted by **thomas** on Wednesday, May 16, 2012 at 6:13pm.

Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why the graph of (fxg)(x) is equivalent to the graph of h(x)=cos x after it has been horizontally compressed by a factor of 1/2. Thanks so much...

## Answer This Question

## Related Questions

- trig function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why ...
- trig function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why ...
- trig function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why ...
- trig function - Suppose f(x)=cos x - sin x and g(x)=cos x + sin x. Explain why ...
- TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...
- trig - The expression 4 sin x cos x is equivalent to which of the following? (...
- trig - Reduce the following to the sine or cosine of one angle: (i) sin145*cos75...
- tigonometry - expres the following as sums and differences of sines or cosines ...
- Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...
- trig - I dont understand this. can you please tell how you got each answer? ...

More Related Questions